2006
DOI: 10.1111/j.1462-2920.2006.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of radiocaesium by arbuscular mycorrhizal fungi to Medicago truncatula under in vitro conditions

Abstract: The capacity of arbuscular mycorrhizal (AM) fungi to take up and translocate radiocaesium (Cs) to their host has been shown using the root-organ culture (ROC) system. However, the absence of photosynthetic tissues, lack of a normal root hormonal balance and incomplete source-sink relationships may bias the bidirectional transfer of elements at the symbiotic interface and complicate transport studies. Accordingly, we developed a novel culture system [i.e. the Arbuscular Mycorrhizal-Plant (AM-P) in vitro culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 53 publications
5
46
0
4
Order By: Relevance
“…However, strict attention was not paid to either the development or presence of arbuscules. Therefore, the observations in our experiment of the presence, development and senescence of Arumtype arbuscule under cryo-SEM coupled with the transport of P and C observed by Dupré de Boulois et al (2006) and Voets et al (2008), respectively, supported the role of arbuscule as an exchange interface and the adequacy of the autotrophic in vitro culture system to sustain this essential attribute of the symbiosis. The presence of vesicles and intraradical spores just behind the apex further demonstrated that AM fungi are able to penetrate the root at the apex zone (Bago and Cano, 2005) and also that intraradical structures such as veAutotrophic in vitro plant cultivation system to study plant-fungal interactions S75 sicles may be located in this zone.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, strict attention was not paid to either the development or presence of arbuscules. Therefore, the observations in our experiment of the presence, development and senescence of Arumtype arbuscule under cryo-SEM coupled with the transport of P and C observed by Dupré de Boulois et al (2006) and Voets et al (2008), respectively, supported the role of arbuscule as an exchange interface and the adequacy of the autotrophic in vitro culture system to sustain this essential attribute of the symbiosis. The presence of vesicles and intraradical spores just behind the apex further demonstrated that AM fungi are able to penetrate the root at the apex zone (Bago and Cano, 2005) and also that intraradical structures such as veAutotrophic in vitro plant cultivation system to study plant-fungal interactions S75 sicles may be located in this zone.…”
Section: Discussionmentioning
confidence: 74%
“…Using a similar in vitro autotrophic cultivation system, Dupré de Boulois et al (2006) demonstrated the transport of P from a hyphal compartment to a root compartment and subsequently to the plant shoot cells via the fungal interface, while the transport of carbohydrates from plant to the AM fungus was investigated by Voets et al (2008). However, strict attention was not paid to either the development or presence of arbuscules.…”
Section: Discussionmentioning
confidence: 99%
“…Jemalong A 17 (SARDI, Australia) were surface disinfected by immersion in sodium hypochlorite (8% active chloride) for 10 min and rinsed in deionized sterile water. Seeds were germinated in Petri plates (90 mm diameter) containing 35 ml of the MSR medium without sucrose and vitamins, 40 solidified with 3 g L ¡1 phytagel and adjusted to pH 5.5 before sterilization (121 C for 15 min). The Petri plates were incubated at 27 C in the dark.…”
Section: Biological Materialsmentioning
confidence: 99%
“…(GEV02) en medio MSR, utilizado para el cultivo de órganos de raíces de zanahoria transformadas (30). El medio carecía de sacarosa y vitaminas, el cual fue utilizado en trabajos realizados para la micorrización in vitro de papa (13), vid (27), Medicago truncatula (26,29) y banano (28).…”
Section: Resultsunclassified